2020
DOI: 10.3390/atmos12010032
|View full text |Cite
|
Sign up to set email alerts
|

Benefit Analysis of the 1st Spanish Air Pollution Control Programme on Health Impacts and Associated Externalities

Abstract: This paper aims to provide scientific support for decision-making in the field of improving air quality by evaluating pollution reduction measures included in the current Spanish policy framework of the 1st National Air Pollution Control Programme (NAPCP). First, the health impacts of air quality are estimated by using the concentrations estimated by multiscale air quality modeling and the recommended concentration–response functions (CRF), specifically as a result of exposure to particulate matter (PM), nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The impact of the Spanish National Air Pollution Control Programme (NAPCP) on air quality and health impacts has been previously assessed at a national level at a coarse resolution (10 × 10 km 2 ) [2,31]. However, the distribution of concentrations of pollutants such as NO 2 in urban areas at microscale get smoothed out in coarse resolution treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the Spanish National Air Pollution Control Programme (NAPCP) on air quality and health impacts has been previously assessed at a national level at a coarse resolution (10 × 10 km 2 ) [2,31]. However, the distribution of concentrations of pollutants such as NO 2 in urban areas at microscale get smoothed out in coarse resolution treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution claimed an estimated seven million lives annually worldwide [1][2][3][4]. The World Health Organization (WHO) and several studies reported that people in urban areas breathe air contaminated with high levels of pollutants [5,6].…”
Section: Introductionmentioning
confidence: 99%